ETİLEN GLİKOL BAZLI NANOAKIŞKANLARIN ÜRETİLMESİ, VİSKOZİTE VE TERMAL ÖZELLİKLERİNİN DENEYSEL İNCELENMESİ - DEMİRPOLAT, AHMET BEYZADE (Fırat Üniveristesi, 2018)
Çalışmamızda, CuO ve ZnO Nanopartikül üretimi yapıldıktan sonra üretilen partiküllerin analizi yapıldı. Nanopartiküllerle beraber saf su, etanol ve etilen glikol malzemeleri kullanılarak üretilen nanoakışkanlar deney düzeneğinden geçirilerek ısı iletim katsayıları (k) ve ısı taşınım katsayıları (h) belirlendi. Reynolds sayısı 1600 civarında olan deneysel ölçümlerde saf suya göre ısı transferinde ZnO' da %16.5 ve CuO' da %13.3 değerinde ortalama iyileşme sağlandı. Akışkanların viskozitelerinin sıcaklığa göre değişimleri belirlendikten sonra grafiksel gösterimi çizildi. Yapılan deneylerde Reynolds sayısı 846 ile 2292 arasında değiştiği gözlemlenmiştir. Ayrıca ısı transfer katsayıları ile Reynolds sayısı arasındaki ilişkiyi veren grafikler çizildi. Anahtar Kelimeler: Isı transfer katsayısı, nanomalzeme, nanoakışkan, Reynolds sayısı

In our work, analysis and measurements of the produced particles were performed after the production of CuO and ZnO nanoparticles. Nanoparticles produced by using pure water, ethanol and ethylene glycol materials with nanoparticles were passed through the experimental setup and the thermal conductivity coefficient (k) and heat transfer coefficients (h) were determined. In experimental measurements with a Reynolds number of around 1600 are provided an average improvement of 16.5% in ZnO and 13.3% in CuO in heat transfer according to pure water. The graph was drawn after the viscosities of the fluids were changed according to the temperature. Reynolds numbers range have been changed from 846 to 2292 in the made experiments. In addition, the graphs showing the relationship between the heat transfer coefficients and the Reynolds number were drawn. Keywords: Heat transfer coefficient, nano material, nanofluid, Reynolds number
Production of ethylene glycol based nanofluids, experi?mental analysis of viscosity and thermal properti?es
Keywords: Makine Mühendisliği